Assessment of the effect of prolonged forced swimming on CD‐1 mice sperm morphology with and without antioxidant supplementation. (29th May 2015) - Rodriguez, I.; Diaz, A.; Vaamonde, D.
Summary: As physical exercise has been shown to negatively affect sperm morphology, this study was undertaken to assess the effect of a 3‐min forced swimming protocol during 50 days, with and without administration of antioxidants [ N ‐acetylcysteine (NAC) and trans‐resveratrol], on sperm morphology in CD‐1 mice. Forty‐four 13‐week‐old CD‐1 mice were randomly allocated to four different groups: mice not submitted to exercise, control group (CG), mice submitted to swimming without administration of antioxidants (EX), mice submitted to swimming that received trans‐resveratrol supplementation [exercise group (EX)+Resv] and mice submitted to swimming exercise that received NAC supplementation (EX+NAC). The EX showed 30.5% of spermatozoa with normal morphology, showing significant differences with regard to the CG, which showed 58.5%. The groups receiving antioxidant supplements showed significantly higher percentages of spermatozoa with normal morphology in comparison with the EX group (EX+Resv: 64.1%, EX+NAC: 48.2%). The imposed model of forced swimming caused alterations in sperm morphology. The antioxidants employed seem to be suitable antioxidants for avoiding exercise‐associated sperm morphology anomalies in prolonged forced swimming exercise. Trans‐resveratrol has proven to be more efficient for this purpose.